THE FORMATION BIONANOTECHNOLOGIES INDUSTRIAL COMPLEXES: THE POTENTIAL OF CLUSTER DEVELOPMENT - N. Zińkowskaya; E. Mokeeva (Вестник университета)
The arguments justify the need for accelerated development of Russian industrial complexes based on biotechnological and nanotechnological innovation.Modern interpretation of bionanotechnological industrial complex (BNT-complex) is presented as an integrated complex based on the convergence of bio - and nano-innovation. The prerequisites and factors of development of BNT-complexes are described in the format of clusters. The main characteristics and problems of cluster development oriented on bionanotechnologies projects in Russia are systematized. The expediency of creation and the functional tasks of cluster Foresight Centre in the framework of development of strategic management systems of bionanoscience clusters are established.